ANALISIS PENGARUH FAKTOR UKURAN PERUSAHAAN, PROFITABILITAS DAN FINANCIAL LEVERAGE TERHADAP INCOME SMOOTHING PADA PERUSAHAAN KEUANGAN DI BURSA EFEK INDONESIA - heri,; Ari Sunardi, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
This study aims to determine the effect of firm size, profitability and financial leverage on income smoothing in financial sector companies listed on the Indonesia Stock Exchange. The research population is companies in the financial sector for three periods that have consecutive profits, complete financial reports for 2016, 2017 and 2018. The method used in this study is multiple linear regression with purposive sampling technique on a research sample of 35 companies. The independent variable consisting of firm size (x1) is proxied by Ln of total assets; profitability (x2) is proxied by net profit margin and financial leverage (x3) which is proxied by debt to total assets. Meanwhile, there is only one dependent variable, namely income smoothing (y). The researcher got the conclusion from this study that x1 and x2 partially have a positive effect on y, while x3 has no effect on y. The variables x1, x2 and x3 simultaneously have a positive effect on variable y